The influence of generative AI on student engagement and academic outcomes in Arabic language learning - Albantani, Azkia Muharom; Abd. Rozak, Abd. Rozak; Sahrir, Muhammad Sabri; Khoiriyyah, Bilqis (Universitas Negeri Malang, Indonesia, 2026)
This study examines the influence of generative artificial intelligence (AI) on student engagement and academic outcomes in Arabic language learning through a quantitative descriptive survey design that captures learners’ perceptions of AI-assisted instruction. Participants were students engaged in Arabic language learning contexts who had used generative AI tools to support their studies. The findings show that learners perceived AI as most effective in facilitating access to learning materials and enhancing vocabulary acquisition, while its role in sustaining focus and supporting writing skill development received the lowest ratings. Qualitative findings further indicate that students valued AI for its immediacy, flexibility, and personalized feedback, alongside concerns about overreliance and reduced depth of engagement. Overall, the results suggest that while generative artificial intelligence provides meaningful pedagogical support in Arabic language learning—particularly for vocabulary development and resource accessibility—intentional instructional guidance remains necessary to address its limitations, contributing novel mixed-methods evidence to the underexplored field of AI-assisted Arabic as a second language learning